Pucangrejo Ecovillage Sebagai Model Desa Ramah Lingkungan Berbasis Ekoteologi Dan Kesadaran Masyarakat - Mustofa, Mahmud Yunus; Alam, Muchammad; Muttaqin, M. in'amul; Baroroh, Kharismatul; Bintiyah, Umi; Nahariyah, Isnaeni; Nisa, Siti Khoirul; Najah Anf, Ahmad Hazim; Zacky N, Muhammad Ali; Roikhatul J, Hikayatul; Malikah, Nur; Nita, Tasya Arum; Fatkhullah, Kamal; Ma’ruf, Rizki Amir; Aprilia, Putri (LPPM Sekolah Tinggi Islam Kendal, 2026)
The low level of awareness among rural communities about the importance of protecting the environment remains a crucial problem. This is rooted in low public participation and in an anthropocentric understanding of environmental ethics. Pucangrejo has great potential, especially in its religious base, to be developed into an ecovillage rooted in Islamic values. This community service program aims to initiate the Pucangrejo Ecovillage model by integrating eco-theological concepts and strengthening collective community awareness. Using the Participatory Action Research (PAR) method, this action involves active collaboration between the research team and the community to diagnose problems, plan actions, implement them, and evaluate outcomes. The results of the community service show that, through PAR, the Pucangrejo community successfully identified the root causes of its environmental problems and independently designed a